Ordonanse królewskie we Francji - Klimaszewska, Anna (Czasopismo Prawno-Historyczne, 2018)
The issue of royal ordinances in France is not a subject avoided by Polish authors, especially in legal history textbooks. However, the information included in these books is fragmentary in its character, and some pieces require verification. In this extensive legislative material one can distinguish specific ordinances (spéciales), which regulate single issues, as well as general ones (générales), which constitute acts pertaining to a wide spectrum of issues, or even detailed codes. The latter, i.e. the ordinances general in their character, can be further divided into two groups. The first of them encompasses the ordinances published between the 14th and the 17th century (I), while the second one includes the so-called Great Ordinances enacted during the reign of Louis XIV and Louis XV (II). The purpose of the following publication is not to perform a detailed characteristic of the ordinances but, first and foremost, to show that although certain significant institutions were regulated by the ordinances from group I in a way which left a permanent mark on the French legal system, the Great Ordinances by Louis XIV and Louis XV, which represent a completely different character from all the previous general ordinances, constituted codes in the strict sense of the word. As a result of that codification work, performed in stages during the reign of two sovereigns, the ancien régime France did not lack general and unified legal acts, created with an understanding of the creative role of law in modifying the reality, regulating select fields of law in a comprehensive way and binding in the entire territory of the country. The code of civil procedure, the code of criminal procedure, as well as the commercial code and the maritime code, were enacted at the time. Some areas of civil law were also regulated. The only thing which was not elaborated, or even approached in those days, was the penal code. Napoleonic codes should be therefore considered as the subsequent chapter of codification activities in France, carried out for the first time by Louis XIV. The popularity of this issue in the Enlightenment literature and the fact that it was a common phenomenon in other European countries is not a sufficient argument to justify applying this term only to those French acts which were enacted in the 19th century and afterwards.